216k views
0 votes
Evaluate function expression −2⋅f(−6)−7⋅g(−7)=

User ZMan
by
4.8k points

2 Answers

4 votes
I hope this is the answer you’re looking for
Evaluate function expression −2⋅f(−6)−7⋅g(−7)=-example-1
User Thilina Dharmasena
by
5.4k points
7 votes

Answer:

11

Explanation:

-2 • f(-6) -7 • g(-7) = ?

As per graph:

f(-6) = 5

g(-7) = -3

Calculation:

-2 • f(-6) -7 • g(-7) =

-2(5) - 7(-3) =

-10 + 21 =

11

User Ngungo
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.